1974
DOI: 10.1136/oem.31.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Bladder tumours and occupation: a coroner's notification scheme

Abstract: Veys, C. A. (1974).British Journal of Industrial Medicine,31, 65-71. Bladder tumours and occupation: a coroner's notification scheme. The disease of bladder cancer accounted for 2 763 male and 1 107 female deaths in England and Wales during 1971. How much of this total is influenced by aetiological factors in the working environment is still largely unknown and is only now beginning to be studied. In order to elucidate this question further, a coroner's notification scheme for all bladder tumours occuring with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Dyestuff and chemical industrial workers, pigment and printing workers, textile dye workers, rubber and cable manufacture workers, gas workers, laboratory workers, handlers of certain rodenticides, and workers in the tar and pitch industries were © 1996-2015 reported to have a high incidence of bladder cancer because they were frequently exposed to arylamines (155,156). Other professions such as bus drivers, leather (including shoe) workers, blacksmiths, machine setters, mechanics, and hairdressers are also high risk groups of bladder cancer.…”
Section: -Aminobiphenylmentioning
confidence: 99%
“…Dyestuff and chemical industrial workers, pigment and printing workers, textile dye workers, rubber and cable manufacture workers, gas workers, laboratory workers, handlers of certain rodenticides, and workers in the tar and pitch industries were © 1996-2015 reported to have a high incidence of bladder cancer because they were frequently exposed to arylamines (155,156). Other professions such as bus drivers, leather (including shoe) workers, blacksmiths, machine setters, mechanics, and hairdressers are also high risk groups of bladder cancer.…”
Section: -Aminobiphenylmentioning
confidence: 99%
“…Studies that followed the sentinel event approach of Rutsein et al have identified case series, then used case by case evaluations to assess the relation of a disease event to work.3 6 The ability to assess aetiology on an individual basis was a criterion for selecting diseases for the United States sentinel event notification system for occupational risks (SENSOR).3 For cancer, and most other diseases on the sentinel events list, it would be difficult to attribute cause on an individual basis, as most cancers with occupational aetiologies also occur in the absence of such exposures. Surveillance would require analytical methods which compare groups.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Hueper (1942) suggested that aromatic amines were responsible for bladder cancer in humans (33). Dyestuff workers, chemical industrial workers, and handlers of certain rodenticides as well as pigment, printing, textile, rubber, cable, gas, tar, pitch and laboratory workers were reported to have a high incidence of bladder cancer because they were frequently exposed to arylamines (34,35). Other professions such as bus drivers, leather (including shoe) workers, blacksmiths, machine setters, mechanics, and hairdressers are also high risk groups of bladder cancer.…”
Section: Carcinogenicitymentioning
confidence: 99%